Modified Atmosphere Does Not Reduce the Efficacy of Phytosanitary Irradiation Doses Recommended for Tephritid Fruit Flies - Vanessa S. Dias; Guy J. Hallman; Olga Y. Martínez-Barrera; Nick V. Hurtado; Amanda A. S. Cardoso; Andrew G. Parker; Luis A. Caravantes; Camilo Rivera; Alexandre S. Araújo; Florence Maxwell; Carlos E. Cáceres-Barrios; Marc J. B. Vreysen; et al. (Insects, 2020)
Phytosanitary irradiation (PI) has been successfully used to disinfest fresh commodities and facilitate international agricultural trade. Critical aspects that may reduce PI efficacy must be considered to ensure the consistency and effectiveness of approved treatment schedules. One factor that can potentially reduce PI efficacy is irradiation under low oxygen conditions. This factor is particularly important because storage and packaging of horticultural commodities under low oxygen levels constitute practices widely used to preserve their quality and extend their shelf life. Hence, international organizations and regulatory agencies have considered the uncertainties regarding the efficacy of PI doses for insects infesting fresh commodities stored under low oxygen levels as a rationale for restricting PI application under modified atmosphere. Our research examines the extent to which low oxygen treatments can reduce the efficacy of phytosanitary irradiation for tephritids naturally infesting fruits. The effects of normoxia (21% O2), hypoxia (~5% O2), and severe hypoxia (< 0.5% O2) on radiation sensitivity of third instars of Anastrepha fraterculus (sensu lato), A. ludens (Loew), Bactrocera dorsalis (Hendel), and Ceratitis capitata (Wiedemann) were evaluated and compared at several gamma radiation doses. Our findings suggest that, compared to normoxia, hypoxic and severe-hypoxic conditioning before and during irradiation can increase adult emergence and contribute to advancement of larval development of tephritid fruit flies only at low radiation doses that are not used as phytosanitary treatments. With phytosanitary irradiation doses approved internationally for several tephritids, low oxygen treatments applied before and during irradiation did not increase the emergence rates of any fruit fly species evaluated, and all treated insects died as coarctate larvae. Thus, the findings of our research support a re-evaluation of restrictions related to phytosanitary irradiation application under modified atmospheres targeting tephritid fruit flies.